Associations between Thinking Styles and Differentiation with Emotional Divorce in Divorcing Couples: The Mediating Role of Dysfunctional Beliefs - Zaker Esfahani, Atefeh; Arefi, Mokhtar; Kakabaraee, Keivan; Chehri, Azita (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: One of the challenges of married life is divorce, whose rising rate has prompted family researchers to investigate its causes and contributors. The present study aimed to investigate the mediating role of dysfunctional beliefs in the relationships between thinking styles and differentiation with emotional divorce in divorcing couples. Methods: This study employed a descriptive correlational research design. The statistical population comprised all divorcing persons visiting clinics and family counseling centers in the city of Isfahan in 2021. A convenient sample of 226 men and women were recruited. They completed the Emotional Divorce Questionnaire, Differentiation of Self Inventory, Thinking Styles Questionnaire, and Dysfunctional Relationship Beliefs Questionnaire. The data analysis involved using Pearson correlation coefficient analysis and structural equation modeling. Results: According to the results, the direct paths from judicial thinking, executive thinking, and dysfunctional beliefs to emotional divorce were statistically significant (P < 0.001). Additionally, the paths from legislative thinking, executive thinking, and differentiation to dysfunctional beliefs were significant (P < 0.001). The indirect effects of legislative thinking (P = 0.006), executive thinking (P = 0.035), and differentiation (P = 0.002) on emotional divorce were statistically significant. Conclusions: Based on the fit indices results, it can be concluded that the assumed model was acceptable. It is important to address the problems caused by emotional divorce and focus on thinking styles, differentiation, and dysfunctional beliefs to improve couples' relationships.